2007
DOI: 10.1093/hmg/ddl487
|View full text |Cite
|
Sign up to set email alerts
|

The ongoing adaptive evolution of ASPM and Microcephalin is not explained by increased intelligence

Abstract: Recent studies have made great strides towards identifying putative genetic events underlying the evolution of the human brain and its emergent cognitive capacities. One of the most intriguing findings is the recurrent identification of adaptive evolution in genes associated with primary microcephaly, a developmental disorder characterized by severe reduction in brain size and intelligence, reminiscent of the early hominid condition. This has led to the hypothesis that the adaptive evolution of these genes has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…Furthermore, Yu et al 101 demonstrated that ASPM is not unusual compared with other anonymously selected regions in the genome, with respect to tests for selection based on population subdivision, haplotype structure and frequency spectrum, and argued that recent positive selection at this locus is unlikely. In addition, subsequent tests for an association between IQ and specific variants of ASPM and MCPH1 proved to be negative 102 .…”
Section: Box 2 Adaptation In Humansmentioning
confidence: 98%
“…Furthermore, Yu et al 101 demonstrated that ASPM is not unusual compared with other anonymously selected regions in the genome, with respect to tests for selection based on population subdivision, haplotype structure and frequency spectrum, and argued that recent positive selection at this locus is unlikely. In addition, subsequent tests for an association between IQ and specific variants of ASPM and MCPH1 proved to be negative 102 .…”
Section: Box 2 Adaptation In Humansmentioning
confidence: 98%
“…Indeed, two genes involved in brain development, MCPH1 and ASPM were both shown to continue to evolve adaptively in the human race. However, as yet none of the fast evolving genes could be linked directly to an adaptive phenotype, such as cognitive ability (e.g., Mekel-Bobrov et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Given the latter result, it is tempting to assume that ascertaining genes under recent positive selection would identify plausible candidate genes for complex traits (but see Mekel-Bobrov et al 2007). Here we present the results of a genome-wide search for genes that exhibit enhanced rate of protein evolution in primates.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 1q21.1 CNVs and brain size found that deletions of the 1q21 region are associated with microcephaly, which is characterised by an abnormally small head, whereas duplications of this region are associated with macrocephaly, which is characterised by an abnormally large head (Brunetti-Pierri et al, 2008). Notably, the most striking trend in human evolution is the rapid increase in brain size over the past 3-4 million years, and the associated increase in complexity and cognitive capacity (Mekel-Bobrov et al, 2007). Because NBPF/DUF1220 is present in remarkably more copies in the human genome than in other primates (Vandepoele et al, 2005;Popesco et al, 2006), it was hypothesised that the NBPF/DUF1220 copy number is correlated with brain size (Dumas & Sikela, 2009).…”
Section: 3mentioning
confidence: 99%